Способ управления сжиганием унитарного твердого топлива в жидкой среде и газогенератор - Барсуков В. Д. Виталий Дементьевич; Басалаев С. А. Сергей Александрович; Голдаев С. В. Сергей Васильевич; Минькова Н. П. Наталья Петровна; Поленчук С. Н. Сергей Николаевич
опубл. 27.05.09